New records of Pestalotioid species associated with leaf spot disease on Camellia sinensis from northern Thailand - Koodalugodaarachchi, Vidyamali; Chethana, K. W. Thilini; Jayawardena, Ruvishika S.; Bundhun, Digvijayini; Aluthmuhandiram, Janith V. S.; Suwannarach, Nakarin; Manawasinghe, Ishara S.; Lumyong, Saisamorn (Phytotaxa, 2024)
Camellia sinensis (L.) Kuntze var. assamica (Miang tea) is widely distributed in northern Thailand due to its traditional and industrial attributes, including black tea and Miang production. In this study, two Pestalotioid taxa associated with C. sinensis leaf spots were collected in Mae Taeng district, Chiang Mai Province, Thailand. Species delineation was based on the evidence from morphological and multi-locus phylogenies using ITS, tub2 and tef1-α. Neopestalotiopsis saprophytica is herein reported as a new record on Camellia sinensis, while Pseudopestalotiopsis chinensis is recorded as a new geographical record from Thailand. The findings of this research have the potential to offer fresh insights into the two previously documented species within the existing fungal community associated with C. sinensis in Thailand. This, in turn, could enhance our comprehension of their interactions with the host plant in the times ahead.